Di Balik Simbolisme Pesan Moral Dzulqornain dalam Al-Qur'an (Analisis Semiotika Roland Barthes) - Siti, Siti Fahimah; Alya Khoironi Muhibbah; Vika Madinatul Ilmi (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
This research investigates the moral message in the story of Dzulqornain found in the Qur'an using Roland Barthes' semiotic analysis. By using Barthes' theories about denotation, connotation and myth, this research finds layers of symbolic meaning in the Dzulqornain story which reflect values ​​such as justice, wisdom and protection of the weak. According to this analysis, the story of Dzulqornain is not just a historical story; it also contains a moral message relevant to modern society and culture. This analysis explores the meaning of the moral message in the Story of Dzulqarnain as a Leader in the Qur'an Surah Al Kahf verses 83-98 using Roland Barthes' Semiotic Theory. Through a Denotative, Connotative and Mythological meaning approach. It was found that this story contains a moral message which includes the characteristics that a leader, especially a Muslim leader, must have, an attitude of obedience to Allah SWT, a sense of responsibility, democracy and establishing closeness between the leader and society. Thus, this story provides in-depth teaching about moral values ​​in a religious context. The results of this research indicate that semiotic techniques are effective in interpreting religious texts. This method allows a deeper understanding of the hidden meanings contained in the Qur'an.